Recreational sport program design, delivery, and management - Barcelona, Robert J. 1970-; Arthur-Banning, Skye; Wells, Mary Sara (Human Kinetics, 2016)
There are more opportunities than ever for employment in recreational sport, which means the need to prepare students with a solid foundation of the design, delivery, and management of recreational sport has never been more critical. Recreational Sport is designed precisely with that need in mind. This text provides a contemporary perspective of recreational sport management, offering a comprehensive picture of recreational sport management for people in or entering all sectors of recreation and leisure, including public, nonprofit, private, and commercial. "We saw a need for broad-based recreational sport programming that reflects the myriad of recreational sport activities and opportunities that are out there," says lead author Robert Barcelona. "To meet those increased needs and interests, people need to have an array of programming and management skills in recreational sport." Barcelona and his coauthors help readers gain those skills in part by simplifying the complicated process of designing and delivering programs in various settings in recreation and leisure services. They present a macrocosm view of recreational sport in communities--a view that reflects the most current, application-based research in the field. Their text places recreational sport squarely in the middle of the recreation and leisure curriculum and is supported by the recreational sport core competencies as developed by Barcelona himself. Those competencies are based on what recreational sport managers need to know and be able to do to grow and succeed in the profession, and they connect with the NIRSA recreational sport competencies developed in 2013. In addition, Recreational Sport offers the following: Coverage for all age groups and sectors in a range of settings and contexts for recreational sport; International perspectives to offer students great insights into career opportunities; The latest theory, research, and real-world approaches to help both students and professionals who program sports; Case studies of real-world issues in recreational sport and examples of theory-to-practice applications. The text comes with an array of online ancillaries that will prove invaluable to both instructors and students. The instructor guide supports and extends the chapter content and offers numerous ideas for learning activities, projects, and topics for papers. It also supplies chapter summaries, glossary terms, and links to websites that contain information for both instructors and students. The test package has multiple-choice, true-or-false, matching, and short-answer questions that can interface with learning management systems, and the presentation package offers a visual overview of the material to help students retain the concepts. "In teaching recreational sport for many years, I know that students first need to grasp the big picture of recreational sports," Barcelona says. "We deliver that big picture in addition to information on design, delivery, and management that every student needs to know to succeed, regardless of what recreational sport organization he or she is a part of." That big-picture element, along with the cutting-edge information on program design, delivery, and management, sets this book apart. In the three parts of the book, students will be able to do the following: Be grounded in the philosophical concepts that define the field; Learn about the core competencies they need to know to deliver successful programs and events; Gain insights about the settings and contexts where recreational sport happens and learn about key ideas, issues, and career opportunities in the field. Recreational Sport is a textbook critical to students' future success in recreational sport management, offering the big-picture view of the field while offering practical guidance in and real-world examples of successful design, delivery, and management of recreational sport programming.